Energy transition: a global analysis of social, economic, and environmental dimensions - Valle, Luisa Poeys do; Vicente, Maristela de Araújo; Meneguelo, Ana Paula; Santos, Maria de Fátima Pereira dos (Brazilian Journal of Production Engineering, 2025)
This study aimed to provide a map of scientific knowledge on the energy transition, capable of guiding future research, identifying collaboration opportunities, and revealing underexplored areas, especially in developing countries. To this end, an exploratory investigation was conducted based on a bibliometric analysis, using data from the Web of Science (WoS) database and the Bibliometrix and Biblioshiny packages to structure and visualize the collected information. The analysis focused on the period from 2019 to 2025, and the results showed an increase from 4 to 473 published articles. The most prominent authors in terms of the number of publications related to the concept of the energy transition are of Chinese nationality. China showed strong collaboration with several countries, as did Europe and the United States. Carbon emissions, economic growth, energy storage, critical minerals, and photovoltaics are identified as relevant topics for future research. Brazil has a relatively low volume of publications on the subject. Considering the country’s energy potential and its variety of renewable sources, it is important to promote national research and strengthen collaboration with international research centers, so that the country remains technologically competitive.
Keywords: energy transition; perspective; economy; technology